The impact of COVID‐19 on the quality of life of older adults receiving community‐based aged care. (8th March 2021) - Siette, Joyce; Dodds, Laura; Seaman, Karla; Wuthrich, Viviana; Johnco, Carly; Earl, Joanne; Dawes, Piers; Westbrook, Johanna I.
Abstract: Objective: To investigate the impact of the COVID‐19 pandemic on the quality of life and social networks of older adults receiving community care services. Methods: Quality of life and social network questionnaires were completed by older adults (n = 21) receiving home care services at three time points (2018, 2019, and during the first Australian COVID‐19 lockdown in 2020). Additional questions about technology use were included in 2020. Results: Older adults' quality of life significantly decreased during the pandemic compared to the prior year. During the pandemic, over 80% used technology to maintain contact with family and friends, and social networks did not change. Conclusion: Government messages and support initiatives directed towards technology adoption among older adults receiving home care may assist with maintaining social connection during COVID‐19. Our findings add to the relatively limited understanding of the impact of the COVID‐19 pandemic on the socio‐emotional well‐being of older people.